Comparative Study on ICT Knowledge among Teachers and UG Students of Universities in India and Tanzania (Indian Journal of Extension Education, 2018)
Information and Communication Technology (ICT) has opened a new visage to globalization in education. Studies over the past decade reflect a striking change in usage pattern of technology amongst teachers and students. Studies depict high utilization patterns of ICTamong teachers and learners. In contrast to its extensively acknowledged importance, computer knowledge and computer related skills demonstrate a wide diversity, both regional and within students and faculties of the educational institutions. A study to assess the extent of ICT knowledge among teachers and UG students of College of Home Science, Professor Jayashankar Telangana State Agricultural University (PJTSAU), Hyderabad, India and Department of Food Science and Technology, Sokoine University of Agriculture (SUA), Tanzania was taken up. Exploratory research design was adopted to conduct the study. The total size of the sample of the study was 260, out of which, 200 were students and 60 were university teachers i.e., 100 students and 30 teachers from each university. The basic knowledge of PJTSAU teachers was up to 94.66 percent, followed by intermediate knowledge of 80.33 per cent and advanced knowledge lesser than the above two levels i.e., 73.5 percent. In the similar manner, SUAteachers gained 87.96 percent, 71 percent and 60 percent in respective levels of knowledge. Similar trend was observed even among the UG students though they scored less than the teachers. The difference in ICT knowledge between teachers and students of the universities is significant.